Inline pin fin heat sink model and thermal performance analysis for central processing unit - Mohd. Annuar, Khalil Azha (2015)
The thermal management issue is common in electronic products such as computers, projectors and others. The trend shows that by increasing the power density, indirectly it will increase the temperature and power dissipation in CPU processor. This is a major challenge to the product designer of electronics cooling system to find an alternative technique to solve the problem. Therefore, in order to control and minimize the heat produced by the CPU's processor, the conventional external heat sink is added to the overall thermal management mechanism. In this paper, 3D simulation inline pin fin heat sink is designed using COMSOL Multiphysics software. The outcome of this study hopefully can shed some light on how to optimize inline pin fin arrangement heat sink design.